Factors of geographical concentration in the tourism industry: evidence from Northeast Caucasus Daniil A. Sitkevich 1, Andrei S. Korotkov - D. A. Sitkevich; A. S. Korotkov (Модернизация, инновация, развитие, 2023)
Purpose: is to study the factors influencing the geographical concentration of hospitality industry enterprises in the republics of the Northeast Caucasus (Ingushetia, Chechnya and Dagestan) – regions that have been the object of an active tourism cluster policy for many years, and which have seen a significant increase in the number of vacationers over the past three years.Methods: the study is based on a hybrid methodology. It uses cartographic data on the prevalence of resolution and collective dining facilities in the Northeastern Caucasus, as well as the results of 29 semi-structured in-depth interviews with representatives of the hospitality industry in Dagestan.Results: the tourist boom that occurred after 2020 in the North Caucasus is not taking place in the special economic zones that have been created. Tourist enterprises are concentrated in those municipalities where the state has not pursued a cluster policy. In addition to the abundance of basic tourist resources (sea, mountains, natural and cultural attractions), the formation of the hospitality industry in these locations has been associated with their transport accessibility, agglomeration effect, the desire of entrepreneurs to take tourists to their native villages, differences in business culture between residents of different municipalities, and the established preferences of tourists themselves. The study also showed that, despite the suitable natural conditions for the creation of ski and beach resorts, the efforts of federal authorities to create tourist clusters were insufficient. The relatively successful cases in the region are associated either with the historically established tourist center, or with the additional efforts of regional authorities.Conclusions and Relevance: insufficient infrastructure policy in the regions hinders the development of tourism not only within special economic zones, but also outside them. Reorientation from the creation of new large resorts to support existing businesses could give a much greater impact on the development of the tourism sector and the modernization of the North Caucasus economy.